Palliative Prognostic Index as a predictor of mortality among geriatric patients with advanced chronic medical conditions - Affizal, Samsudin; Yon Lek, Yap; Yoon Doong, Loh; Htwe Chit, Htwe; Mohamad Adam, Bujang (Malaysian Medical Association, 2022)
Introduction: This study is to validate Palliative Prognostic Index (PPI) as a tool for six months prognostication in geriatric patients with advanced chronic medical conditions and to identify other independent prognostic markers of survival. Methods: This was a prospective and observational study of 108 geriatric patients conducted at Pusat Jantung Hospital Umum Sarawak (PJHUS) Kota Samarahan and Sarawak General Hospital (SGH). The PPI scores were calculated and determined at the time of admission. Mortality is considered as the primary outcome. Sensitivity and specificity analysis were conducted to test the accuracy of PPI. The ideal cut-off value for PPI and other associated markers were determined based on the highest value of Youden Index. Cox regression analysis and survival analysis were applied to test the association between potential markers within six months. Results: PPI score has a significant association with survival within six months based on univariate and multivariate analyses (p<0.05). Total PPI had a hazard ratio of 1.56 (95% Confidence Interval (95%CI): 1.33,1.57). The study shows PPI reported area under the curve-ROC of 0.945 with p<0.001. PPI score with cut-off value of six reports the highest accuracy in predicting death within six months with sensitivity and specificity of 88.6% and 90.6%, respectively. Total PPI score of >6 with serum albumin level ≤25, the sensitivity and specificity tested were 100.0%. Conclusion: PPI has the potential to be a useful and significant predictor of mortality within six months in the geriatric population with an advanced chronic medical condition. This study also re-emphasised the strong prognostic role of other markers such as Palliative Performance Scale, Barthel Index, and serum albumin level. This study has identified that hypoalbuminemia cut-off value of 25g/dL analysed against PPI score of >5 revealed extremely high accuracy of prognostication for mortality.